2015
DOI: 10.1063/1.4914769
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards developing neutron tolerant magnetostrictive and piezoelectric transducers

Abstract: Current generation light water reactors (LWRs), sodium cooled fast reactors (SFRs), small modular reactors (SMRs), and next generation nuclear plants (NGNPs) produce harsh environments in and near the reactor core that can severely tax material performance and limit component operational life. To address this issue, several Department of Energy Office of Nuclear Energy (DOE-NE) research programs are evaluating the long duration irradiation performance of fuel and structural materials used in existing and new r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These materials tend to have much lower d33 values but much higher radiation tolerance. Aluminum nitride, bismuth titanate niobate, and zinc oxide were tested in the Massachusetts Institute of Technology Research Reactor [21,33] to a fast neutron fluence of 8.8 × 10 20 n/cm 2 . Of these, only aluminum nitride exhibited sufficient performance to be considered for long-term in-core applications.…”
Section: State Of Technology For Advanced Reactor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials tend to have much lower d33 values but much higher radiation tolerance. Aluminum nitride, bismuth titanate niobate, and zinc oxide were tested in the Massachusetts Institute of Technology Research Reactor [21,33] to a fast neutron fluence of 8.8 × 10 20 n/cm 2 . Of these, only aluminum nitride exhibited sufficient performance to be considered for long-term in-core applications.…”
Section: State Of Technology For Advanced Reactor Applicationsmentioning
confidence: 99%
“…Most other available alloys with high magnetostriction contain cobalt, which may be a concern due to the fact that activation of the element turns it into a strong gamma emitter. Very few magnetostrictive materials have been tested in an in-core environment, but several (Remendur, Galfenol, and two Arnokrome alloys) were included in the aforementioned Massachusetts Institute of Technology Research Reactor irradiation test [20,21,33]. The Galfenol and Remendur samples were interrogated in real-time, while the Arnokrome samples were "drop ins" that were examined during post-irradiation testing.…”
Section: Magnetostrictive Technologiesmentioning
confidence: 99%
“…This paper is based on the Penn State Ph.D. Thesis of Dr. Brian Reinhardt [ 14 ] and will discuss the details of the experiment for bismuth titanate (BiTi). The results for the other sensor materials have been discussed in detail elsewhere [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Overview Of Reactor Projectmentioning
confidence: 99%
“…A table of candidate materials for longitudinal wave generation is provided below in Table 3; however, this is only the first step. The final column in Table 3 is of substantial importance as it has been found that crystal structure plays a significant role in radiation tolerance of ceramics [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74].…”
Section: Piezoelectric Materials For Radiation Environmentmentioning
confidence: 99%